Carbon dioxide (CO2) laser cut quality of acrylic using different feed rate and constant power - Abd Halim, Abdullah @ Shafei (2008)
Laser are widely used as cutting tools that obtain high quality end product. Laser can cut many type of material includes metals, plastic, rubber, and ceramics. In this project, the samlpes of acrylic (Polymethyl Methacrylate, PMMA) were cut used Carbon Dioxode (CO2) laser cutting machine with different feed rate and affect of feed rate on cut quality has been studied. The cut qualities examined were surface roughness and kerf width. Optimum power of CO2 laser machine at FKM lab used is about 25.5W. In checking cut quality process, Perthometer was used to measured surface roughness and Image Analyzer was used to measured kerf width. The both cut qaulity parameters are analyzed and graph were plloted between feed rate versus cut quality. From the graph, reelationship between feed rate and cut quality were discused. As a result, increasing feed rate led to increasing on surface roughness and the kerf width decrease when the feed rate increase. The top and bottom surfaces of the acrylic specimen indicated that the top kerf width was slightly larger than the bottom kerf width. For get good cut quality, surface roughness and kerf width are kept at minimum value. From the result, it can conclude that feed rate has effect on surface roughness and kerf widt quality. To obtain better result, the experiment is able to improve in term use another method to analyzed result and consider more parameter that can effect the cut quality.